Genome-wide profile analysis of the Hsp20 family in lettuce and identification of its response to drought stress - Zhang, Qinqin; Dai, Bowen; Fan, Mi; Yang, Liling; Li, Chang; Hou, Guangguang; Wang, Xiaofang; Gao, Hongbo; Li, Jingrui (Frontiers in Plant Science, 2024)
Heat shock protein 20 (Hsp20) plays a very important role in the response to abiotic stressors such as drought, but in lettuce (Lactuca sativa L.), this gene family is poorly understood. This study used bioinformatics methods to identify 36 members of the lettuce Hsp20 family, which were named LsHsp20-1~LsHsp20-36. Subcellular localization results revealed that, 26 members of the LsHsp20 protein family localized to the cytoplasm and nucleus. Additionally, 15 conserved domains were identified in the LsHsp20 protein family, with the number of amino acids ranging from 8 to 50. Gene structure analysis revealed that 15 genes (41.7%) had no introns, and 20 genes (55.5%) had 1 intron. The proportion of the LsHsp20 secondary structure was random coil>alpha helix>extended strand>beta turn. Chromosome positioning analysis indicated that, 36 genes were unevenly distributed on 9 chromosomes, and 4 pairs of genes were collinear. The Ka/Ks ratio of the collinear genes was less than 1, indicating that purifying selection dominated during L. sativa evolution; 13 pairs of genes were collinear in lettuce and Arabidopsis, and 14 pairs of genes were collinear in lettuce and tomato. A total of 36 LsHsp20 proteins were divided into 12 subgroups based on phylogenetic analysis. Three types of cis-acting elements, namely, abiotic and biotic stress-responsive, plant hormone-responsive and plant development-related elements, were identified in the lettuce LsHsp20 family. qRT-PCR was used to analyze the expression levels of 23 LsHsp20 genes were significantly up-regulated on the 7th or 14th day of drought treatment, the expression levels of two genes (LsHsp20-12 and LsHsp20-26) were significantly increased by 153-fold and 273-fold on the 14th and 7th days of drought treatment, respectively. The results of this study provide comprehensive information for research on the LsHsp20 gene family in lettuce and lay a solid foundation for further elucidation of Hsp20 biological functions, providing valuable information on the regulatory mechanisms of the LsHsp20 family in lettuce drought resistance.